Semantics in space systems architectures. (March 2016) - Romero, Alessandro; Schneider, Klaus; Ferreira, Maurício
Abstract Costs, life cycles, technologies and agreements between stakeholders and organizations make space systems unique with respect to the complexity. A commonly accepted technique to address part of this complexity is to model and to maintain space systems architectures through the life cycle of their space programs. The benefits may range from supporting consistent model definitions and maintenance up to supporting analysis and verification. Space systems architectures have been modeled using UPDM (unified profile for DoDAF And MODAF; a UML profile). In fact, UPDM argues that it provides a clearer understanding of the semantics behind specific views and viewpoints. Nonetheless, while UML defines its semantics imprecisely using plain text and variation points, UPDM does not define any semantics. In this paper, we evaluate an extension of fUML (semantics of a foundational subset for executable UML models) as a semantics for space systems architectures. The extension of fUML as a synchronous language (synchronous fUML) provides a limited, but formally precise and deterministic, form to describe structure and behavior in UML. Through the combination of this semantics with UPDM, a precise language supporting a standardized meta-model emerges for the definition of space systems architectures. At the end, a simplified case study covering the operational view (OV-*) is presented. Our initial results show that synchronous fUML is able to offer a precise and deterministic semantics for UPDM.